Seniority in Germany: New Evidence on Returns to Tenure for Male Full-time Workers - Riphahn, Regina Therese; Orlowski, Robert (Journal for labour market research, 2008)
This study uses recent data taken from the German Socioeconomic Panel (2002-2006) to evaluate the extent of and heterogeneity in returns to tenure for men in East and West Germany, employed in both the private and the public sector. We find significantly different wage patterns in East- and West Germany as well as between the private and public sector. Independent of the particular subsample, the application of the Altonji-Shakotko estimation approach yields minute and insignificant returns to tenure and more substantial returns to experience. The profile of the East German wage structure is surprisingly flat: after the first ten years of experience - and in contrast to the situation in West Germany - there appear to be no returns to additional general human capita
WiSo-Import:2015-03-26:1037
Keywords: Transformation; seniority; returns to tenure; private and public sector; earnings patterns